HIST1H1B Promotes Basal-Like Breast Cancer Progression by Modulating CSF2 Expression - Liao, Ruocen; Chen, Xingyu; Cao, Qianhua; Wang, Yifan; Miao, Zhaorui; Lei, Xingyu; Jiang, Qianjin; Chen, Jie; Wu, Xuebiao; Li, Xiaoli; Li, Jun; Dong, Chenfang (Frontiers in Oncology, 2021)
Background Basal-like breast cancer (BLBC) is associated with a poor clinical outcome; however, the mechanism of BLBC aggressiveness is still unclear. It has been shown that a linker histone functions as either a positive or negative regulator of gene expression in tumors. Here, we aimed to investigate the possible involvement and mechanism of HIST1H1B in BLBC progression. Experimental design We analyzed multiple gene expression datasets to determine the relevance of HIST1H1B expression with BLBC. We employed quantitative real-time PCR, transwell assay, colony formation assay, and mammosphere assay to dissect the molecular events associated with the expression of HIST1H1B in human breast cancer. We studied the association of HIST1H1B with CSF2 by ChIP assay. Using tumorigenesis assays, we determine the effect of HIST1H1B expression on tumorigenicity of BLBC cells. Results Here, we show that the linker histone HIST1H1B is dramatically elevated in BLBC due to HIST1H1B copy number amplification and promoter hypomethylation. HIST1H1B upregulates colony-stimulating factor 2 (CSF2) expression by binding the CSF2 promoter. HIST1H1B expression promotes, whereas knockdown of HIST1H1B expression suppresses tumorigenicity. In breast cancer patients, HIST1H1B expression is positively correlated with large tumor size, high grade, metastasis and poor survival. Conclusion HIST1H1B contributes to basal-like breast cancer progression by modulating CSF2 expression, indicating a potential prognostic marker and therapeutic target for this disease.